Simple Liquid Chromatography–Tandem Mass Spectrometry Method for Quantitation of Total and Free Aprepitant and Its Active N-Dealkylated Metabolites in Human Plasma. Issue 3 (June 2021) - Naito, Takafumi; Suzuki, Yusuke; Shibata, Kaito; Kawakami, Junichi
Abstract : Background: Aprepitant, an antiemetic selective neurokinin-1 receptor antagonist, is primarily metabolized to the active N -dealkylated form (ND-AP) and then converted to its carbonyl form (ND-CAP) in humans. This study developed a simple liquid chromatography–tandem mass spectrometry method using electrospray ionization for the quantitation of plasma total and free aprepitant and its N- dealkylated metabolites and used them to analyze patient plasma. Methods: Free aprepitant and ND-AP in plasma were fractionated using centrifugal ultrafiltration. The analytes in plasma or their ultrafiltered specimens treated with triethylamine/acetonitrile were isocratically separated using a 3-μm octadecylsilyl column with a total run time of 10 minutes and scanned using positive ion electrospray ionization. Results: The calibration curves of total aprepitant, ND-AP, and ND-CAP were prepared at concentration ranges of 50–2500, 20–1000, and 5–250 ng/mL, respectively, whereas that of free aprepitant and ND-AP were at a concentration range of 2–150 ng/mL. The intraassay and interassay accuracy and imprecision values were 93.5%–107.7% and 94.6%–103.3%, and 2.1%–7.5% and 1.0%–8.9%, respectively. Aprepitant and its metabolites did not exhibit any matrix effects or instabilities in the plasma specimens. In cancer patients receiving oral aprepitant, the plasma concentration ranges of total aprepitant, ND-AP, and ND-CAP, and free aprepitant and ND-AP were 137–2170, 104–928, 22.4–97.6, 8.11–60.0, and 3.53–56.0 ng/mL, respectively. The median plasma free fraction proportion of aprepitant and ND-AP was 4.14% and 4.90%, respectively. Conclusions: The present developed method showed an acceptable analytical performance and can be used to evaluate total and free aprepitant and its N- dealkylated metabolites in patient plasma.